Nursing professionals' attitudes toward biostatistics: an international web-based survey - Ocakoglu, Gokhan; Kaya, Mehmet Onur; Can, Fatma Ezgi; Kuyuk, Sema Atis; Macunluoğlu, Aslı Ceren (My University, 2019)
Objectives: The present study, an international web-based survey, was focused on four aims: to obtain nursingprofessional’s self-reported statistical knowledge levels and how this knowledge varies by research area, toinvestigate and specify when biostatistics courses should be taught in nursing education and to identify thekey statistical methods relevant to nursing education.Methods: A total of 448 nursing professionals from five continents and 52 countries participated in our study.For the data comparison, Kruskal-Wallis test and Mann-Whitney U test were applied.Results: The results indicate that while nursing professionals place an emphasis on biostatistics education, themajority state that biostatistics education should be taken both at the undergraduate and postgraduate level andthe participants also believe that taking a biostatistics course is useful for their occupation. A biostatisticseducation should also emphasize the necessity of consulting to a biostatistician when planning a study.Conclusion: Our study provides information regarding self-reported levels of biostatistical knowledge ofnursing professionals by research area and academic position, and provides guidance regarding the idealsemester for administering a biostatistics course.
Keywords: Tıbbi İnformatik; Eğitim; Eğitim Araştırmaları; Hemşirelik; İstatistik ve Olasılık